2016
DOI: 10.1101/093377
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Roughness of a transmembrane peptide reduces lipid membrane dynamics

Abstract: Transmembrane domains integrate proteins into cellular membranes and support their function. The capacity of these prevalently a-helical structures in mammals to influence membrane properties is poorly understood. Combining experiments with molecular dynamics simulations, we provide evidence that helical transmembrane peptides with their rough surface reduce lateral mobility of membrane constituents. The molecular mechanism involves trapping of lipid acyl chains on the rough surface and segregation of choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Interestingly, the augmented lipid mobility (shorter relaxation times) probed by Laurdan and Patman in oxPL-containing membranes match the faster lateral diffusion of phospholipids measured by fluorescence correlation spectroscopy (FCS) in those systems. This general rule of the correspondence between the time of TDFS relaxation and the time of lateral diffusion of lipids was frequently observed; see e.g., (Olšinová et al, 2018). There are however certain differences between the lateral diffusion of lipids and the local mobility probed by TDFS.…”
Section: Oxidized Model Lipid Membranessupporting
confidence: 54%
See 1 more Smart Citation
“…Interestingly, the augmented lipid mobility (shorter relaxation times) probed by Laurdan and Patman in oxPL-containing membranes match the faster lateral diffusion of phospholipids measured by fluorescence correlation spectroscopy (FCS) in those systems. This general rule of the correspondence between the time of TDFS relaxation and the time of lateral diffusion of lipids was frequently observed; see e.g., (Olšinová et al, 2018). There are however certain differences between the lateral diffusion of lipids and the local mobility probed by TDFS.…”
Section: Oxidized Model Lipid Membranessupporting
confidence: 54%
“…In protein science this pre-requisite is achieved by site-selected labelling, while the location of the chromophore of amphiphilic membrane probes can be determined by quenching experiments and molecular dynamic (MD) simulations. Together with MD simulations the TDFS approach identified how molecular parameters like membrane curvature (Sýkora et al, 2005;Magarkar et al, 2017), lipid composition (Jurkiewicz et al, 2005;Jurkiewicz et al, 2006;Olżyńska et al, 2007;Jurkiewicz et al, 2012b;Melcrová et al, 2019), presence of ions (Vácha et al, 2010;Jurkiewicz et al, 2012b;Pokorna et al, 2013;Melcrová et al, 2016;Melcrová et al, 2019), presence of pharmaceuticals (Först et al, 2014), membrane binding of peptides (Macháň et al, 2014;Olšinová et al, 2018), or lipid oxidation (Beranova et al, 2010;Volinsky et al, 2011;Jurkiewicz et al, 2012c;Vazdar et al, 2012;Štefl et al, 2014;Kulig et al, 2015b;Kulig et al, 2016) control the hydration and mobility in the headgroup region of bilayers. On the protein side the TDFS again combined with simulations demonstrated the significance of hydration and mobility in enzyme enantioselectivity (Jesenská et al, 2009;Stepankova et al, 2013;Sykora et al, 2014) as well as demonstrated how lateral membrane pressure changes the hydration profile in transmembrane channels (Fischermeier et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…251 This effect influences a larger region of the membrane due to the collective behavior of lipids, 252 thus systemically reducing lipid mobility in protein-rich membranes. 251,253,254 According to the Mattress model of Bloom and Mouritsen, 255 the hydrophobic mismatch between lipid bilayer and the length of the hydrophobic TMD can cause segregation of lipids within membranes. This prompts the formation of lipid nanodomains surrounding one TMD or more TMDs with similar hydrophobic thickness.…”
Section: Protein-induced/modulated Lipid Domainsmentioning
confidence: 99%
“…Interactions of nonannular lipids with proteins are longer lasting compared to the highly transient bouncing of annular lipids around TMDs. Integral proteins have been shown to reduce the mobility of annular lipids due to nonspecific trapping of lipid acyl chains on the rough surface of helical TMDs . This effect influences a larger region of the membrane due to the collective behavior of lipids, thus systemically reducing lipid mobility in protein-rich membranes. ,, According to the Mattress model of Bloom and Mouritsen, the hydrophobic mismatch between lipid bilayer and the length of the hydrophobic TMD can cause segregation of lipids within membranes.…”
Section: Protein-induced/modulated Lipid Domainsmentioning
confidence: 99%